Assessment of seismic design provisions for confined masonry using experimental and numerical approaches. (15th October 2021) - Borah, Bonisha; Singhal, Vaibhav; Kaushik, Hemant B
Highlights: Quasi-static cyclic tests on half-scale specimens of confined masonry walls demonstrated that the aspect ratio plays a major role in the damage pattern and failure modes. Simplified finite element numerical simulation was used to predict the nonlinear lateral load behaviour and to provide better understanding of the damage pattern and strain distribution. Design-to-experimental strength ratios unveiled a large variation in the safety margins adopted in different codes against shear and flexural failure of CM walls. The study established that the existing design codes need to be further improved by carrying out more experimental and numerical studies considering variations in all important parameters on which the performance of CM buildings depends. Abstract: Confined Masonry (CM) buildings have been embraced in many countries due to simple construction methodology, affordability, and effectiveness in resisting the seismic loads safely in comparison to unreinforced masonry buildings. However, most of the available seismic design codes for CM are still under development with several gap areas remaining to be addressed. The present study is a step towards filling this gap by assessing the seismic design provisions for CM walls. Three CM walls of different aspect ratios (2.0, 1.5, and 1.0) were designed based on present international practice and corresponding half-scale specimens were tested under quasi-static cyclic loading. The results were compared in terms of damage, hysteresis behavior, deformation response, and yielding of longitudinal reinforcements in tie-columns. The test results highlighted the important role of aspect ratio, especially on the initiation of shear or flexural cracking in different members. The tie-columns of the squat wall suffered major damage quite early. A finite element numerical study was also carried out to simulate the key behavior of the tested specimens and gain a better visual understanding on the development of stresses and strains in different members of the specimens. The methods recommended in the existing seismic design codes were then used to predict the design values of shear and flexural strengths of the CM walls tested in the present and the past experimental studies by considering all the associated safety factors. Finally, a comparative design vs actual lateral strength assessment was carried out to compare the global safety margins obtained from different codes. It was observed that some codes provide considerable safety margins, whereas some do not, even after considering all the safety factors. This necessitates a need for extensive investigation to improve the design provisions of CM buildings in different parts of the world.